The plastic dynamics and failure analysis of ship broadside protection structures subjected to contacted UNDEX: energy dissipation model and simulation. (3rd April 2022) - Wang, Hao; Pei, Da-ming; Zhang, Pan; Gan, Lin
ABSTRACT: The plastic dynamic response and failure modes of ship broadside protection structures (SBPSs) subjected to contacted underwater explosion (UNDEX) are investigated. A novel engineering analytical model is proposed to evaluate the failure mechanisms and energy absorption characteristics. A numerical model considering the fluid-structure interaction (FSI) is built to analyze the plastic dynamic responses. The results show that the main energy dissipation parts of the SBPS are outside panel, separate bulkhead and inner expandable bulkhead. The maximum error between the analytical model and numerical results is 28%. Parametric studies show that charge position has a significant effect on the damage severity. The difference in the crevasse size can reach up to 40%. The selection of the thickness for shock wave venting bulkhead outside plate and bulkhead stiffener is most important, which coincides with the theoretical solution. The above method could provide worthy guidance to the design of the energy-absorbing structure of underwater weapons defense cabin of naval ships.